1978
DOI: 10.1258/002367778781088431
|View full text |Cite
|
Sign up to set email alerts
|

Depilatory effects of certain chemicals during the first hair growth cycle in sucking mice

Abstract: The chemicals were administered, subcutaneously, orally or topically. Generally, the depilation produced in the mice by mimosine or cyclophosphamide differed from that produced by the steroid analogues tested. In the first 2 cases almost completely naked mice were commonly seen, while in the steroid-treated groups the complete inhibition of all hair fibres was rare. This is discussed in relation to the effects of the same compounds on wool growth in sheep. When related to bodyweight, the doses of cyclophospham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

1980
1980
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
9
1
Order By: Relevance
“…Reis and Tunks (1982) have shown that ethionine, an analogue of methionine, is an inhibitor of wool growth and may cause shedding of the fleece. However, in contrast to various compounds investigated by Panaretto et al (1978), it did not induce hair loss in mice during their first cycle of hair growth. In the study reported in this paper, the effects of cycloleucine and reduced glutathione were investigated in sheep in an attempt to obtain further information relevant to the mode of action of ethionine as an inhibitor of wool growth.…”
Section: Introductioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Reis and Tunks (1982) have shown that ethionine, an analogue of methionine, is an inhibitor of wool growth and may cause shedding of the fleece. However, in contrast to various compounds investigated by Panaretto et al (1978), it did not induce hair loss in mice during their first cycle of hair growth. In the study reported in this paper, the effects of cycloleucine and reduced glutathione were investigated in sheep in an attempt to obtain further information relevant to the mode of action of ethionine as an inhibitor of wool growth.…”
Section: Introductioncontrasting
confidence: 69%
“…Tests with sucking mice in their first hair-growth cycle were carried out, using Sydney White strain mice, as described by Panaretto et al (1978). Most groups consisted of 10 mice with five serving as untreated controls.…”
Section: Experimental Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commencing when they were 6 days old with an average weight of 4 g, 40 mice were injected subcutaneously once daily for 3 days with a solution of L-mimosine as described by Panaretto et al (1978); the total dose of mimosine averaged 2·7 mg per mouse. Seven days after the first injection of mimosine, 20 treated mice showing at least 90 % depilation were selected.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the diets and experimental treatments are given in the relevant references or in the description of each experiment. Sucking mice were maintained as described by Panaretto et al (1978).…”
Section: Experimental Procedures With Animalsmentioning
confidence: 99%